72-hour hospital readmission of older people after hospital discharge with home care services. Issue 3 (3rd July 2019) - Cunha Ferré, María Florencia; Gallo Acosta, Cristian Matías; Dawidowski, Adriana Ruth; Senillosa, Mónica Beatríz; Scozzafava, Silvana María; Saimovici, Javier Matías
ABSTRACT: In this retrospective cohort study in Argentina, risk factors for hospital readmission of older adults, within 72 hours after hospital discharge with home care services, were analyzed. Fifty-three percent of unplanned emergency room visits within 72 hours after hospital discharge resulted in hospital readmissions, 65% of which were potentially avoidable. By multivariate logistic regression, low functionality, pressure ulcers, and age over 83 years predicted hospital readmission among emergency room attendees. It is important to identify and analyze barriers in current home care services and the high-risk population of hospital readmission to improve the strategies to avoid adverse outcomes.